If it's not what You are looking for type in the equation solver your own equation and let us solve it.
n in (-oo:+oo)
(1/3)*(9*n+12) = 0
1/3*(9*n+12) = 0
9*n+12 = 0 // - 12
9*n = -12 // : 9
n = -12/9
n = -4/3
n = -4/3
| (-1)-(-16)-(-2+7)= | | (x+2)+(3x-4)=18 | | 5x+40/8 | | 3m-1=6 | | 2a-3/5a+7 | | 1/2(4x-1) | | 4y-11=5y+7 | | (3/2x+1)-(10/x-3)=1 | | 9(5x+12)+6x=4x+3 | | 5x-7=56-2x | | 6y-1=4y+1 | | 1/3(6+3)=2x-5 | | 15=4x^2-2x+4 | | v=xyz | | a^3c-3bc-a^3+3b=0 | | z/3.2+7.42 | | 10=4x^2-2x+4 | | 42-6x-13=-29 | | 5x^3=-3xy+2 | | y/0.4=-4.2 | | 100-4x=132+24 | | 5-3(7-3x)=9(x-1) | | 4/5d-1/5d=7/10 | | 7(x+1)=5x+1/2 | | x+2.7=6.0 | | .6*600+.2x=.3(600+x) | | x(x+3)2x=23 | | -139-10x=9x+15 | | -7.6-(-10.1)= | | 11x-4x=2x-7 | | 4log(x-4)=-2log(x+1) | | 90-(2x-4)= |